Analisis Jaringan Kerja dengan Metode Critical Path Method (CPM) dan Model Program Linier - Purba, Switamy Angnitha (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
Network analysis is part of a project that requires time for each network activity. To produce a particular project there is more than one job/event that must be done. Each job/event is interconnected and placed in order according to the management of its implementation. In network projects, it is necessary to plan and supervise systematically, in order to obtain work efficiency. The network is represented in symbols and arrows. In this study, the problem-solving network analysis was solved using the CPM (Critical Path Method) method and with a linear programming model using the help of excel-solver and Lingo. This study aims to compare the two methods in solving network analysis problems. Based on the analysis, it is found that by using the CPM method, more critical paths are obtained than the linear programming method. With the increasing number of critical paths obtained, it is hoped that the management can determine project priorities to maintain the project schedule to be completed on time.